"Listening" to Science: Science Podcasters' View and Practice in Strategic Science Communication. Issue 2 (April 2022) - Yuan, Shupei; Kanthawala, Shaheen; Ott-Fulmore, Tanya
We have witnessed an increasing amount of science podcasts, and it has emerged as an important venue for science communication. From a strategic science communication perspective, this study investigated how science podcasters view science communication–related goals and objectives, as well as the tactics they use in producing science communication content based on the theory of planned behavior. A survey ( N = 147) with science podcasters showed that they see excitement and interest in science as their most prioritized objective and present the value of science over time. In addition, our results showed that podcasters frequently use communication tactics, but it may not have resulted from planned strategic communication action. The findings of this study provide initial insight into podcasters' views and practice as part of the science communication effort.